MORTALITAS DAN TINGKAT EKSPLOITASI IKAN BREK (Barbonymus balleroides Val. 1842) DI SUNGAI SERAYU KABUPATEN BANJARNEGARA, JAWA TENGAH - Rumondang Rumondang (Universitas Musamus, Merauke, Papua, 2016)
Study of Barbonymus balleroides in the Serayu River, where there is Mrica Reservoir. The damming activity has led to habitat fragmentation which affects the pattern of food habits, was conducted from October 2012 to January 2013. Fish samplings were done using a 3-meter long nets and gill nets with 3 mesh size (¾, 1 ½ and 2 inches) measuring 20 meters in length and 2 meters in width, and electrofishing. Fish sampling was carried out in three zones (downstream, middlestream, and upstream), which consisted of 6 stations. There were 1,602 fishes captured and total length are ranged from 64 to 238 mm. The average condition factor of female fish was larger than male. The middle zone had a higher condition factor than the other zones. The asymptotic length of fish (L∞) was 253 mm, the coefficient growth (k) was 1 per year, and the theoretical age when the fish length was equal to zero (t0) -0,087 so that the growth equation of von Bertalanffy of Barb was Lt=253(1-e -1(t+0.087)). The highest natural mortality rate of Barb was found in the downstream zone (0.73), and then by the middle zone (0.58) and the upstream zone (0.57). The highest exploitation rate of Barb was found in the downstream zone (0.93), and then the upper zone (0.70), and middle zone (0.57). The exploitation rate Val.ue of Barb in upstream area of Serayu river was exceeded the optimum exploitation rate Val.ue of 0.5.